Design of a single operator : single balloon enteroscope (SO-SBE) and therapeutic procedure through the SO-SBE - Soon, Yong Jin. (2009)
The Single Balloon Enteroscope (SBE) is a novel way of examining the small intestine by using a conventional endoscope in tandem with an overtube. Although the method of SBE proves to be effective and feasible in the area of enteroscopy, it also includes some drawback due to its complicating operating procedures. A second operator is needed to assist the main endoscopist by holding on to the overtube and perform inserting/retracting action as instructed. Therefore, this does not only limit the full control to the main endoscopist, but it also reduces the efficiency of the entire process as a second party is needed to assist the main endoscopist to achieve his/her intention.